Digit ratio (2D:4D) and transgender identity: new original data and a meta-analysis - Siegmann, Eva-Maria; Müller, Tobias; Dziadeck, Isabelle; Mühle, Christiane; Lenz, Bernd; Kornhuber, Johannes (Scientific Reports, 2020)
Previously reported associations between second-to-fourth digit length ratio (2D:4D), a proxy for prenatal androgen load, and transgender identity have been inconsistent. The objectives of the present study were to provide additional original data and an updated meta-analysis concerning this association. In a study of 464 participants, we compared the 2D:4D of transgender individuals with age- and sex-matched controls. Patients were recruited at a specialized psychiatrist’s medical office, whereas controls were hired via flyers, advertisements, and as convenience sample. A random-effects meta-analysis of the literature (17 samples, n = 3674) also quantifies the overall magnitude of the difference in 2D:4D between transgender individuals and controls. In our study providing new original data, we found a significantly higher (i.e. feminized) left-hand 2D:4D in the male-to-female transgender (MtF) identity [mean age: 32.3 (18; 61)] than in the male control group [mean age: 34.5 (18; 65)] with a Cohen’s d = 0.271. Concordantly, the meta-analytic results suggest a significant difference in 2D:4D among MtF individuals compared to male controls [g = 0.153; 95% CI (0.063; 0.243)], which was even more pronounced when individuals had been diagnosed by a clinician instead of self-identified as transgender [g = 0.193; 95% CI (0.086; 0.300)]. In both studies, no significant results were revealed for female-to-male transgender individuals [mean age: 26.1 (18; 53)] versus female controls [mean age: 27.2 (18; 55)]. This original investigation and the updated meta-analysis clarify the association between transgender identity and 2D:4D indicating the influence of prenatal androgen on the development of gender identity in subjects born as males.
CRIS-Team Scopus Importer:2020-11-20